ANALYSIS OF THE INCIDENCE AND RISK FACTORS FOR LEAD-RELATED COMPLICATIONS FOLLOWING PACEMAKER IMPLANTATION - Dr. Abdul Sami ,Dr. Malik Faisal Iftekhar ,Dr Muzafar Ali Surhio ,Dr Mashooque Ali Dasti ,Dr. Ghulam Mahdi Jamro ,Dr. Amjad Ali (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective: We aim to identify the prevalence of lead-related complications and determine the specific risk factors contributing to their occurrence.  Methods: A retrospective observational study was conducted at Hayatabad Medical Complex Peshawar, from 1st January 2018 to 31st December 2018. The study included all patients who underwent pacemaker implantation during the study period. Patients with incomplete medical records or missing data were excluded from the analysis. The primary outcome measure was the incidence of lead-related complications following pacemaker implantation. Lead-related complications encompassed various issues such as lead dislodgement, lead fracture, lead insulation failure, and lead-related infections.